The Influence of Agricultural Exports, High-Technology Exports, Investment, and Regulatory Quality on the Gross Domestic Product of APEC Member Countries - Angga Nur Firdaus; Marselina Djayasinga; Toto Gunarto; I Wayan Suparta; Asih Murwiati (Eduvest - Journal of Universal Studies, 2024)
Gross Domestic Product (GDP) is one of the macroeconomic indicators that reflects the level of welfare of a country's population. The APEC (Asia-Pacific Economic Cooperation) forum has the main goal of promoting economic growth and enhancing prosperity in the Asia-Pacific region. This is done by encouraging and facilitating more open trade and investment in the region. APEC member countries have different export characteristics, namely agricultural exports and high-technology exports. This study analyzes the influence of agricultural exports, high-technology exports, Foreign Direct Investment, and regulatory quality on the Gross Domestic Product of APEC member countries. The research data used are secondary data from the World Bank from 2011 to 2020, analyzed using the Fixed Effect Model approach of panel data regression method using E-Views 12. The results show that simultaneously, agricultural exports, high-technology exports, Foreign Direct Investment, and regulatory quality have a significant influence on the economies of APEC member countries. Partially, high-technology exports and regulatory quality have a positive and significant impact, while agricultural exports and Foreign Direct Investment have a positive but not significant impact on GDP. APEC countries should focus on productivity by harnessing technology and achieving inclusive economies for societal welfare.